Impact of a refined nursing model combined with early exercise rehabilitation on patients with chronic heart failure under a risk assessment strategy - Sun, Yan; Jin, Haiqin; Wu, Lingsha (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe treatment focus for patients with chronic heart failure (CHF) remains on acute resuscitation and maintenance during the stabilization phase. Despite significant advances in CHF management, treatment outcomes and disease control remain suboptimal. This study investigates the impact of a refined nursing model incorporating risk assessment strategies, combined with early exercise rehabilitation, on patients with CHF.MethodNinety cases of patients with CHF admitted to our hospital between February 2024 and November 2024 were selected and divided into the control group and the study group according to the randomized numerical table method, with 45 cases in each group. The control group carried out routine nursing care under a traditional model, and the study group applied a refined nursing model under a risk assessment strategy, combined with early exercise rehabilitation for nursing care, on the basis of the traditional model.ResultThe left ventricular ejection fractions (LVEFs) of CHF patients in the study group were significantly higher after cardiac ultrasound care compared with the control group, B-type natriuretic peptide was significantly lower, and 6-minute walk distance (6-MWD) was significantly longer. Walk distance (6-MWD) was significantly prolonged. The difference between the two groups was statistically significant (t = 2.172, P = 0.033; t = 2.097, P = 0.039; t = −4.594, P < 0.001). After care, patients in the study group had significantly higher scores on the activity of daily living scale and significantly lower scores on the Minnesota living with heart failure questionnaire than those in the control group. The difference between the two groups was statistically significant (t = −4.027, P < 0.001; t = 2.198, P = 0.031).ConclusionA refined nursing model under a risk assessment strategy, combined with early exercise rehabilitation nursing, can significantly improve the cardiac function of patients with chronic heart failure and also the quality of life of such patients.